Apakah Bank Syari’ah Sudah Syari’ah? Pengalaman Budaya Organisasi di BPR Syariah Adam Bengkulu, Indonesia - Ihsan Rahmat; Satiana Rafita Lestari; Rodiyah Rodiyah (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
Sharia banks in Indonesia are growing and developing significantly. Meanwhile, previous studies have found many work practices that have not demonstrated sharia principles. This study explains the internalization of Islam into the organizational culture in Islamic banks. Bank Pembiayaan Rakyat Syariah (BPRS) Adam in Bengkulu City was appointed as a single case study. A semi-structured interview technique has been used, in addition to direct observation and several document collections such as bank profiles, meeting minutes, photos of activities, and monthly work recaps. All data were grouped, while interviews and observations were transcribed, coding, and categorized keywords. This article shows that the internalization of Islam in organizations is carried out simultaneously through written administrative regulations. The activities carried out are congregational prayers at Zuhr time, reading several hadiths after prayer, weekly recitations in the office, reading of Yasin's letter every Friday morning, and monthly recitations, which are carried out alternately at employees' homes. In addition, several forms of Islamic values are also reflected in many practices: greeting, greeting, and smiling to customers, speaking according to etiquette to coworkers, and wearing clothes that conform to Islamic standards. However, this was done before BPRS Adam transformed into a sharia bank. This study has shown that Islamic organizational culture in Islamic banks can be codified and implemented when the organization pays special attention to it. This, at the same time, rejects the findings of previous studies that Islamic organizations do not necessarily apply Islamic principles.